The Effect of Strategic Thinking on the Quality of Work Life: a case study of group of economic institutions In the state of M'sila - Belouadah, Ahmedseifeddine; Djelloulo, Mohamed; mehdi, omar (Finance and Business Economies Review, 2022)
This study aims to know about the impact of strategic thinking on the quality of work life from the point of view of senior and middle management employees in a group of economic institutions in M'sila state, the study relied on the descriptive analytical method in building the theoretical part and on the questionnaire tool in order to obtain the required information. the research process revealed an impact of strategic thinking on the quality of job life, and the presence of an impact of the dimensions of strategic thinking on the quality of career, except for the strategic intent dimension, and the study concluded with a set of recommendations, the most important of which is the need to acquire sufficient knowledge about the external environment variables to ensure a balance between the well-being of the human factor and the aspirations of the institution in the long-term.